Haplotypes of the RANK and OPG genes are associated with chronic arthralgia in individuals with and without temporomandibular disorders. Issue 9 (September 2017) - Bonato, L.L.; Quinelato, V.; Borojevic, R.; Vieira, A.R.; Modesto, A.; Granjeiro, J.M.; Tesch, R.; Casado, P.L.
Abstract: The aim of this study was to evaluate the association between genetic polymorphisms and the comorbid presence of chronic systemic arthralgia in patients with articular temporomandibular disorders (TMD). Subjects were evaluated for the presence of TMD and asked about the presence of chronic joint pain. Four groups were included in the study: articular TMD and systemic arthralgia ( n  = 85), no articular TMD and systemic arthralgia ( n  = 82), articular TMD and no systemic arthralgia ( n  = 21), no articular TMD and no systemic arthralgia (control, n  = 72). A total of 14 single nucleotide polymorphisms in the OPG, RANK, and RANKL genes were investigated. In the statistical analysis, a P -value of <0.05 was considered significant. For the OPG gene, an association was observed between the group with chronic arthralgia and joint TMD and the control group ( P  = 0.04). There was also a tendency towards an association of the haplotype CGCCAA with an increased risk of developing chronic joint pain, even in the absence of TMD ( P  = 0.06). For the RANK gene, the AGTGC haplotype was associated with the lowest risk of presenting chronic joint pain in individuals without TMD ( P  = 0.03). This study supports the hypothesis that changes in the OPG and RANK genes influence the presence of chronic joint pain in individuals with and without TMD.